2017
DOI: 10.1016/j.apmr.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Guidelines to Promote Cardiometabolic Health in Spinal Cord Injured Humans: Time to Raise the Intensity?

Abstract: Spinal cord injury (SCI) is a life-changing event that, as a result of paralysis, negatively influences habitual levels of physical activity and hence cardiometabolic health. Performing regular structured exercise therefore appears extremely important in persons with SCI. However, exercise options are mainly limited to the upper body, which involves a smaller activated muscle mass compared with the mainly leg-based activities commonly performed by nondisabled individuals. Current exercise guidelines for SCI fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 167 publications
5
52
0
1
Order By: Relevance
“…In able-bodied adults, higher intensity exercise such as interval training leads to superior increases in VO 2 max than moderate exercise which is beneficial to overall health status. In fact, Nightingale et al [32] proposed that HIIT may be a viable alternative to MICE in persons with SCI to markedly improve fitness and health status. This is an important consideration since some data show that chronic MICE does not alter many outcomes related to cardiometabolic health in persons with SCI [33].…”
Section: Discussionmentioning
confidence: 99%
“…In able-bodied adults, higher intensity exercise such as interval training leads to superior increases in VO 2 max than moderate exercise which is beneficial to overall health status. In fact, Nightingale et al [32] proposed that HIIT may be a viable alternative to MICE in persons with SCI to markedly improve fitness and health status. This is an important consideration since some data show that chronic MICE does not alter many outcomes related to cardiometabolic health in persons with SCI [33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of this work has concentrated on cardiorespiratory exercise modalities in which the exercise bouts are applied in short intervals of (sub) maximal ('high-intensity interval training' [HIIT]) or supramaximal ('sprint interval training' [SIT]) intensity exercise bouts, interspersed with periods of lowintensity or resting recovery. There is now a convincing body of evidence demonstrating that, at least in the short-term, both HIIT and SIT are associated with very similar, and in some cases superior, cardiometabolic health benefits compared with currently recommended moderate-intensity continuous training (MICT [19][20][21]; ). However, multiple sprint repetitions combined with the need for recovery intervals mean that many HIIT and SIT protocols are not as time-efficient as often claimed, with most taking~22-40 min per training session [19].…”
Section: Introductionmentioning
confidence: 99%
“…Participation in LTPA among the population with SCI globally consistently has shown that no more than 52% [5][6][7][8][9] undertake such activities on a regular basis. Although LTPA is an important component for improving positive psychological well-being and quality of life among a population with chronic SCI [10], performing LTPA alone may not necessarily be sufficient to provide health benefits or raise cardiometabolic fitness [11]. In addition, activities of daily living among individuals with SCI who use wheelchairs, as opposed to the able-bodied, may not be adequate for producing intensities that are health beneficial [12,13], though some studies have reported otherwise [14,15].…”
Section: Introductionmentioning
confidence: 99%